Perlindungan Hukum bagi Anak yang Melakukan Tindak Pidana Penyalahgunaan Narkotika - Debi Riski Aulia Putri (Faculty of Law Universitas Muhammadiyah Metro, 2025)
Children represent the nation's paramount investment and hope for its future sustainability. This article aims to investigate the protective measures for children who engage in narcotics-related criminal activities and the legal repercussions they may face if implicated in such situations. Consequently, the government is very concerned with the development of children, particularly in providing them with the most comprehensive education possible. This study employs a normative methodology, using materials from library research, various literary journals, books, magazines, and other online media, while referencing Law Number 11 of 2012 about Juvenile Justice. One of Indonesia's deficiencies is its drug legislation, which remains fraught with several inadequacies. Consequently, children's engagement in drug addiction and trafficking often results from imitation or the impact of adult persuasion. This study elucidates the nature of legal protection and the types of punishments applicable to youngsters who engage in narcotics-related criminal activities.